Arginine Vasotocin Preprohormone Is Expressed in Surprising Regions of the Teleost Forebrain - Rodriguez-Santiago, Mariana; Nguyen, Jessica; Winton, Lin S.; Weitekamp, Chelsea A.; Hofmann, Hans A. (Frontiers in Endocrinology, 2017)
Nonapeptides play a fundamental role in the regulation of social behavior, among numerous other functions. In particular, arginine vasopressin (AVP) and its non-mammalian homolog, arginine vasotocin (AVT), have been implicated in regulating affiliative, reproductive, and aggressive behavior in many vertebrate species. Where these nonapeptides are synthesized in the brain has been studied extensively in most vertebrate lineages. While several hypothalamic and forebrain populations of vasopressinergic neurons have been described in amniotes, the consensus suggests that the expression of AVT in the brain of teleost fish is limited to the hypothalamus, specifically the preoptic area (POA) and the anterior tuberal nucleus (putative homolog of the mammalian ventromedial hypothalamus). However, as most studies in teleosts have focused on the POA, there may be an ascertainment bias. Here we revisit the distribution of AVT preprohormone mRNA across the dorsal and ventral telencephalon of a highly social African cichlid fish. We first use in situ hybridization to map the distribution of AVT preprohormone mRNA across the telencephalon. We then use qPCR to assay AVT expression in the dorsomedial telencephalon, the putative homolog of the mammalian basolateral amygdala. We find evidence for AVT preprohormone mRNA in regions previously not associated with the expression of this nonapeptide, including the putative homologs of the mammalian extended amygdala, hippocampus, striatum, and septum. In addition, AVT preprohormone mRNA expression within the basolateral amygdala homolog differs across social contexts, suggesting a possible role in behavioral regulation. We conclude that the surprising presence of AVT preprohormone mRNA within dorsal and medial telencephalic regions warrants a closer examination of possible AVT synthesis locations in teleost fish, and that these may be more similar to what is observed in mammals and birds.